NLRP6-Dependent Pyroptosis-Related lncRNAs Predict the Prognosis of Hepatocellular Carcinoma - Zhang, La; Zhang, Xiuzhen; Zhao, Wei; Xiao, Xinyu; Liu, Shanshan; Peng, Qiling; Jiang, Ning; Zhou, Baoyong (Frontiers in Medicine, 2022)
Abstract Background: Pyroptosis, a novel pro-inflammatory type of programmed cell death, is involved in the tumorigenesis of various cancers. Recent findings have implicated long non-coding RNAs (lncRNAs) in the serial steps of cancer development. However, the expression and prognostic signatures of pyroptosis-related lncRNAs in hepatocellular carcinoma (HCC) remain largely unknown. Therefore, here, pyroptosis-related lncRNAs in HCC were identified, and a pyroptosis-related lncRNA prognostic model was constructed for HCC. Methods: Thirty-four pyroptosis-related genes were obtained from previous reviews, and gene expression data were collected from The Cancer Genome Atlas (TCGA) database. Spearman’s correlation test was used to identify potential pyroptosis-related lncRNAs. Cox and LASSO regression analyses were used to construct a prognostic model. Subsequently, receiver operating characteristic (ROC) curves were constructed to assess the model’s predictive ability for the overall survival (OS) of HCC patients. CytoHubba was used to screen potential hub genes. Finally, clinical samples from HCC patients were used to verify the expression of the hub gene. Results: There were nine pyroptosis-related differentially expressed lncRNAs in HCC, and a prognostic model with four pyroptosis-related lncRNAs was constructed with an area under the ROC curve (AUC) of approximately 0.734. Single-sample gene set enrichment analysis and TCGA revealed different immune infiltration and immune checkpoints between the high- and low-risk groups. Moreover, these lncRNAs are closely related to the pyroptosis-related gene, NLRP6, which may be considered a hub gene. NLRP6 was lower-expressed in HCC samples, and patients with lower expression of NLRP6 had the longer OS, suggesting a favorable prognosis for HCC patients with lower levels of NLRP6. Conclusions: A NLRP6-dependent pyroptosis-related lncRNA prognostic model appears to be accurate and specific, and the genes included in this model may be potential predictors and therapeutic targets in HCC patients.